Surface-modified hexagonal boron nitride particles and methods for making same.

Surface-modified hexagonal boron nitride particles with a partially reduced graphene oxide layer address the poor dispersibility and affinity issues, achieving improved thermal conductivity and mechanical strength in resin compositions.

JP7661077B2Active Publication Date: 2025-04-14KRI INC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2021045422
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-19
Publication Date
2025-04-14
Estimated Expiration
2041-03-19

AI Technical Summary

Technical Problem

Hexagonal boron nitride particles have poor dispersibility in resins due to low affinity, leading to surface peeling and void formation, and existing surface modification methods, such as adsorbing graphene oxide, are not universally effective across different production methods and particle shapes and sizes.

Method used

Surface-modified hexagonal boron nitride particles are created by adsorbing a partially reduced graphene oxide layer, which increases the adsorption amount by 1.5 times or more compared to using graphene oxide alone, regardless of the particle shape or size.

Benefits of technology

The increased adsorption of partially reduced graphene oxide improves the affinity of hexagonal boron nitride particles with resins, resulting in a thermally conductive resin composition with enhanced mechanical strength and thermal conductivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007661077000001
    Figure 0007661077000001
  • Figure 0007661077000002
    Figure 0007661077000002
Patent Text Reader

Abstract

To provide a method for producing hexagonal boron nitride particles, and to provide surface-modified hexagonal boron nitride particles with good resin affinity in which the amount of adsorption is increased by a partially reduced graphene oxide adsorption layer, regardless of the particle shape and size.SOLUTION: Surface-modified hexagonal boron nitride particles of the present invention have a partially reduced graphene oxide adsorption layer on a surface of surface-untreated hexagonal boron nitride particles. The amount of the partially reduced graphene oxide adsorption layer is not less than 1.5 times the amount of the graphene oxide adsorption layer of the surface-modified hexagonal boron nitride particles having the graphene oxide adsorption layer.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to surface-modified hexagonal boron nitride particles. [Background technology]

[0002] As electronic and communication devices become smaller and denser, and LED lighting devices become more powerful, the importance of efficiently dissipating the heat generated is growing, and the development of resin materials with high thermal conductivity is underway. Conventionally, resin materials have been mixed with metal oxide powders such as graphite and alumina to increase their thermal conductivity. However, the use of graphite raises the problem of high electrical conductivity of the resin material. Metal oxides, on the other hand, do not provide sufficient thermal conductivity.

[0003] To address these problems, nitrides such as hexagonal boron nitride particles, which have no electrical conductivity but high thermal conductivity, are expected to be used. Hexagonal hexagonal boron nitride particles are scaly (plate-like), and when viewed from the side, they have flat surfaces (the (0001) basal surface in the hexagonal system, hereafter referred to as the (0001) surface) and particle side surfaces (the primary cylindrical surface in the hexagonal system) on the top and bottom of the particle. The flat surfaces on the top and bottom of the particle have very few functional groups, so they have low affinity with resin. This causes problems such as poor dispersibility in resin and easy peeling at the interface between the hexagonal boron nitride particle surface and the resin, which creates voids. In addition, since hexagonal boron nitride particles have high thermal conductivity anisotropy in the (0001) plane direction, multiple particles are granulated to solve this problem. In this case, the surface of the granulated particles has a high proportion of (0001) faces, so the same problem occurs.

[0004] In order to improve the affinity between hexagonal boron nitride particles and resin, a method of adsorbing graphene oxide onto the surface of hexagonal boron nitride particles (Patent Document 1) has been proposed. In this method, by simply mixing hexagonal boron nitride powder with a graphene oxide aqueous dispersion, graphene oxide is adsorbed onto the surface of hexagonal boron nitride particles, and the surface of the hexagonal boron nitride particles is modified with graphene oxide. Since graphene oxide has low electrical conductivity, it can be applied to high thermal conductive materials with excellent insulation and voltage resistance. However, even if the same hexagonal boron nitride is used, if the manufacturing method or particle shape and size are different, there is a problem that the amount of graphene oxide adsorbed is small or almost not adsorbed. Therefore, it cannot be said to be a general-purpose surface modification method for hexagonal boron nitride particles. In addition, Patent Document 1 describes surface modification with reduced graphene oxide, but the graphene oxide adsorbed on the hexagonal boron nitride particles is reduced, so the above problem does not fundamentally change.

[0005] In addition, reduced graphene oxide, which is obtained by completely reducing graphene oxide, becomes hydrophobic and aggregates in water, so it cannot be uniformly adsorbed onto the surface of boron nitride particles. Therefore, after adsorbing graphene oxide, a reduction treatment is performed to produce boron nitride particles modified with reduced graphene oxide (Patent Document 1, Non-Patent Document 1, etc.). [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2019-001701 A [Non-patent literature]

[0007] [Non-Patent Document 1] HUANG Tao et al.,Advanced Composites Letters,2016,Vol.25,Iss.6,p.147-150 Summary of the Invention [Problem to be solved by the invention]

[0008] The present invention has been made to solve the above-mentioned problems, and an object of the present invention is to provide surface-modified hexagonal boron nitride particles in which the adsorption amount is increased by a partially reduced graphene oxide adsorption layer, regardless of the manufacturing method or particle shape / size of the hexagonal boron nitride particles. [Means for solving the problem]

[0009] As a result of intensive research to solve the above-mentioned problems, the inventors discovered that using partially reduced graphene oxide increases the amount adsorbed onto boron nitride particles compared to using graphene oxide, and thus completed the present invention.

[0010] The surface-modified hexagonal boron nitride particles of the present invention are surface-modified hexagonal boron nitride particles having a partially reduced graphene oxide adsorption layer on the surface of a surface-untreated hexagonal boron nitride particle, and the amount of the partially reduced graphene oxide adsorption layer is 1.5 times or more the amount of the graphene oxide adsorption layer of the surface-modified hexagonal boron nitride particles having a graphene oxide adsorption layer. That is, the surface-modified hexagonal boron nitride particles have sheet-like partially reduced graphene oxide adsorbed onto surface-untreated hexagonal boron nitride particles, and the weight adsorption amount of the partially reduced graphene oxide is 1.5 times or more, and preferably 1.7 times or more, of the weight adsorption amount of the adsorbed graphene oxide of the surface-modified graphene oxide having sheet-like graphene oxide adsorbed thereon.

[0011] In a preferred embodiment, the partially reduced graphene oxide exhibits an absorption peak in a wavelength region in a visible / ultraviolet / visible absorption spectrum that is larger than that of graphene oxide and smaller than that of reduced graphene oxide.

[0012] The method for producing surface-modified hexagonal boron nitride particles of the present invention includes the steps of adding a reducing agent to an aqueous dispersion of graphene oxide to prepare an aqueous dispersion of partially reduced graphene oxide, mixing a powder of surface-untreated hexagonal boron nitride particles with the aqueous dispersion of partially reduced graphene oxide until the supernatant is no longer colored, and recovering and drying the solid from the liquid. Effect of the Invention

[0013] According to the present invention, it is possible to provide hexagonal boron nitride particles whose surfaces are modified with at least 1.5 times, and preferably at least 1.7 times, by weight of partially reduced graphene oxide, as compared to when graphene oxide is adsorbed, regardless of the manufacturing method of the hexagonal boron nitride particles or the particle size and shape. This makes it possible to improve the affinity of all hexagonal boron nitride particles with resins, thereby making it possible to provide a thermally conductive resin composition with superior mechanical strength and thermal conductivity. [Brief description of the drawings]

[0014] [Figure 1] UV-visible absorption spectrum of aqueous dispersion of partially reduced graphene oxide. [Diagram 2] Secondary electron image of surface-modified hexagonal boron nitride particles and carbon and boron mapping images obtained by Auger electron spectroscopy. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] Preferred embodiments of the present invention will be described below, but the present invention is not limited to these embodiments.

[0016] The surface-modified hexagonal boron nitride particles of the present invention have a partially reduced graphene oxide adsorption layer on the surface of surface-untreated hexagonal boron nitride particles. Since this partially reduced graphene oxide adsorption layer is in direct contact with the surface of the hexagonal boron nitride particles, when the hexagonal boron nitride particles are mixed with a resin, the affinity of the interface between the resin and the hexagonal boron nitride particles is improved while the interface thermal resistance between the hexagonal boron nitride particles and the resin is minimized, so that the high thermal conductivity property of the hexagonal boron nitride particles is not impaired.

[0017] <Hexagonal boron nitride> Hexagonal boron nitride, which is sold as a thermal conductive filler, contains scaly particles (D 50 Average particle diameter: 1-30 μm. Plate-like particles with increased thickness (D 50 Average particle diameter: 3 to 150 μm. Granular particles (D 50 The average particle diameter is about 20 to 100 μm. As the surface-modified hexagonal boron nitride particles of the present invention, any shape and size of hexagonal boron nitride described above can be used as long as they have not been subjected to any surface treatment.

[0018] Partially reduced graphene oxide adlayer The partially reduced graphene oxide adsorption layer is present on the surface of hexagonal boron nitride particles, and its amount varies depending on the shape of the hexagonal boron nitride particles. This is because the surface area on which the partially reduced graphene oxide adsorption layer is formed is reduced in the case of granular hexagonal boron nitride particles compared to flake or plate hexagonal boron nitride particles. The partially reduced graphene oxide adsorption layer is 0.90×10 per unit surface area in the case of flake or plate hexagonal boron nitride particles. -7 ~1.2×10 -6 g / cm 2 , preferably 0.95 x 10 -7 ~1.0×10 -6 g / cm 2 , more preferably 1.0×10 -7 ~0.95×10 -6 g / cm 2 It is 0.90×10 -7 g / cm 2If the amount is less than 1.2×10, the area on the surface of the hexagonal boron nitride particles that does not have the partially reduced graphene oxide adsorption layer will be large, and the effect of surface modification will be reduced. -6 g / cm 2 If the amount is more than this, the surface modification effect is not observed in proportion to the increase. For granular hexagonal boron nitride particles, the amount per unit surface area is 0.35×10 -7 ~1.0×10 -6 g / cm 2 , preferably 0.40 x 10 -7 ~0.95×10 -6 g / cm 2 , more preferably 0.45×10 -7 ~0.90×10 -6 g / cm 2 0.35×10 -7 g / cm 2 If the amount is less than 1.0×10, the area on the surface of the hexagonal boron nitride particles that does not have the partially reduced graphene oxide adsorption layer will be large, and the effect of surface modification will be reduced. -6 g / cm 2 If the amount is greater than this, the surface modification effect will not be observed in proportion to the increase.

[0019] The amount of the partially reduced graphene oxide adsorption layer can be known by quantitative analysis of carbon using a carbon / sulfur analyzer. Since the quantitative value of carbon is easily affected by the carbon / sulfur analyzer and the combustion improver, in this specification, the analytical value obtained by analysis using the LECO CS844 carbon / sulfur analyzer and the combustion improver: W and LECO CEL (registered commercial) II manufactured by LECO is adopted. The surface area of ​​the hexagonal boron nitride particles can be known by measuring the BET specific surface area. In addition, as described later, the amount of partially reduced graphene oxide adsorbed on the hexagonal boron nitride particles can be experimentally known, and this method is sufficient to grasp the approximate amount. The partially reduced graphene oxide adsorption layer on the surface of the hexagonal boron nitride particles can be confirmed by Auger spectroscopy or micro-Raman spectroscopy.

[0020] The partially reduced graphene oxide adsorption layer may be a single layer or multiple layers, but a single layer is preferred. If it is multiple layers, when the surface-modified hexagonal boron nitride particles of the present invention are mixed with a resin to form a composite material, peeling may occur due to some external factor, and the peeled partially reduced graphene oxide may adversely affect the physical properties of the composite material. For example, the electrical conductivity of partially reduced graphene oxide increases depending on the reduction degree, so if the peeled partially reduced graphene oxide is further reduced due to some factor, the insulating property of the composite material decreases. The number of layers can be evaluated by an atomic force microscope or an electron microscope. Note that another partially reduced graphene oxide is not adsorbed on the partially reduced graphene oxide adsorbed on the surface of the boron nitride particles. This is because, just as the partially reduced graphene oxide is dispersed in water without agglomeration due to electrical repulsion by the oxygen-containing functional group or hydration of the oxygen-containing functional group, there is a similar interaction between the partially reduced graphene oxide adsorbed on the surface of the boron nitride particles and another partially reduced graphene oxide, and aggregation (=adsorption) does not occur. In this respect, it can be said that the amount of the partially reduced graphene oxide adsorption layer is proportional to the coverage area of ​​the hexagonal boron nitride particle surface, especially when the partially reduced graphene oxide is a monolayer sheet. A monolayer partially reduced graphene oxide adsorption layer can be formed by adsorbing a monolayer of partially reduced graphene oxide.

[0021] Partially reduced graphene oxide In general, graphene oxide is purple Graphene with oxygen-containing functional groups that exhibit an absorption peak around 230 nm in the visible-light absorption spectrum, reduced graphene oxide is purple In the visible-light absorption spectrum, it is recognized as reduced graphene oxide, which shows an absorption peak in the wavelength region greater than about 265 nm. It is known that this absorption peak shifts to longer wavelengths depending on the reduction state of graphene oxide.

[0022] According to the above general understanding, the partially reduced graphene oxide used in the present invention has intermediate properties, being in a more reduced state than graphene oxide, but not as reduced as reduced graphene oxide. This is suggested by the fact that the partially reduced graphene oxide used in the present invention has an absorption peak on the longer wavelength side than graphene oxide and on the shorter wavelength side than 265 nm. Note that the absorption peak positions of graphene oxide and reduced graphene oxide may slightly deviate from 230 nm and 265 nm depending on the measurement conditions, so in this specification, the absorption peak position of graphene oxide at 230 nm and the absorption peak position of reduced graphene oxide at 265 nm are not absolute values. In addition, when the degree of oxidation of graphene oxide, which is generally expressed by the carbon / oxygen ratio, is low, the amount of oxygen-containing functional groups may be almost the same as that of partially reduced graphene oxide, but , Purple Since the absorption peak of the visible absorption spectrum is around 230 nm, the carbon / oxygen ratio cannot be used as an index of the degree of reduction.

[0023] The partially reduced graphene oxide used in the present invention is in an intermediate reduced state between graphene oxide and reduced graphene oxide, and is therefore more hydrophobic than graphene oxide but not as hydrophobic as reduced graphene oxide. As a result, the partially reduced graphene oxide maintains a similar dispersion in water to graphene oxide and is easily adsorbed onto the hydrophobic surface of hexagonal boron nitride particles by van der Waals forces (particularly hydrophobic bonds).

[0024] Both graphene oxide and partially reduced graphene oxide are polygonal sheets with molecular-level thickness. The size of the sheet can be defined in various ways, but in this specification, the equivalent circle diameter calculated from the sheet area measured by image analysis of atomic force microscope or electron microscope images is used. The reason for this is that the equivalent circle diameter can define the size more objectively than the maximum length of the sheet measured from atomic force microscope or electron microscope images.

[0025] The average equivalent circle diameter of the partially reduced graphene oxide is 20 μm or less, preferably 18 μm or less, and more preferably 16 μm or less. Partially reduced graphene oxide larger than 20 μm is not necessary in consideration of the size of the target boron nitride particles. Although there is no particular lower limit for the average equivalent circle diameter, partially reduced graphene oxide smaller than 1 μm is not preferred because it is difficult to cause adsorption or, even if adsorbed, it is easily peeled off. Note that the D of hexagonal boron nitride particles is 50 When the average particle size is 2 μm or less, if large partially reduced graphene oxide is used, a composite is likely to be formed in which multiple hexagonal boron nitride particles are adsorbed to the partially reduced graphene oxide. When such a composite is combined with a resin, it is not preferable because it causes a decrease in insulation properties. 50 When using hexagonal boron nitride particles with an average particle size of 2 μm or less, this can be achieved by using partially reduced graphene oxide with an average equivalent circle diameter of 4 μm or less.

[0026] <Aqueous dispersion of partially reduced graphene oxide> The partially reduced graphene oxide aqueous dispersion can be prepared by reducing commercially available graphene oxide or a graphene oxide aqueous dispersion prepared by the improved Hummers method under appropriate conditions. The reduction method is preferably a chemical reduction using a reducing agent that can be performed in an aqueous medium. As the reducing agent, conventionally known water-soluble sodium borohydride or hydrazine hydrate can be used, but reduction using ascorbic acid is preferable in terms of the removability of residues and the fact that nitrogen is not introduced into the graphene skeleton. The reduction state can be controlled by the amount of reducing agent used, the reduction temperature, and the reduction time. The reduction temperature is 80°C or higher, preferably 90°C or higher, because the reduction is performed in an aqueous medium. The appropriate amount of reducing agent used and the reduction time vary depending on the amount of graphene oxide and the amount of oxygen-containing groups to be reduced, so they can be appropriately adjusted by looking at the absorption peak position of the ultraviolet-visible absorption spectrum of the partially reduced graphene oxide aqueous dispersion obtained by the reduction treatment. The partially reduced graphene oxide dispersion obtained by the reduction treatment can be placed in a dialysis tube and dialyzed (purified) with ion-exchanged water to obtain a partially reduced graphene oxide aqueous dispersion. If the graphene oxide used as the raw material is a single layer, the partially reduced graphene oxide will also be a single layer. However, to be sure, it is preferable to perform a peeling treatment by ultrasonic irradiation after the reduction and purification treatment, centrifuge the treated liquid, and use the supernatant. In some cases, the pH of the aqueous dispersion can also be adjusted. Whether the partially reduced graphene oxide used is a single layer can be evaluated by an atomic force microscope or an electron microscope. The concentration of the partially reduced graphene oxide in the aqueous dispersion is not particularly limited, but it is easy to handle if it is within the range of 0.1 to 0.5 w%.

[0027] (Preparation of surface-modified flake-like, plate-like, or granular hexagonal boron nitride particles) The surface-modified scaly, plate-like or granular hexagonal boron nitride particles of the present invention are dispersed by adding scaly, plate-like or granular hexagonal boron nitride particle powder to the partially reduced graphene oxide aqueous dispersion and stirring, shaking or, if necessary, using a dispersing device such as a homogenizer. When the hexagonal boron nitride particle powder is dispersed in the partially reduced graphene oxide aqueous dispersion in this process, precipitation occurs and the color of the supernatant (partially reduced graphene oxide aqueous dispersion layer) becomes lighter. The supernatant finally becomes colorless and transparent. This is because the partially reduced graphene oxide is adsorbed to the hexagonal boron nitride particles. It is preferable to end the addition of the hexagonal boron nitride particles to the partially reduced graphene oxide aqueous dispersion at a stage where the supernatant remains colored, so that the hexagonal boron nitride particles do not become excessive and hexagonal boron nitride particles with a small amount of adsorption of the partially reduced graphene oxide do not occur. The degree of coloration of the supernatant can be determined using the peak intensity of the ultraviolet-visible absorption spectrum, and the end point of the addition of the hexagonal boron nitride particles is preferably the point when the peak intensity of the supernatant becomes about 1 / 10 of the peak intensity of the partially reduced graphene oxide dispersion before the addition.

[0028] The particles are recovered from the dispersion of hexagonal boron nitride particles having partially reduced graphene oxide adsorbed thereon by filtration or centrifugal sedimentation, and then dried at room temperature or, if necessary, by heating and drying at about 50 to 70°C, to obtain the surface-modified hexagonal boron nitride particles of the present invention as a powder.

[0029] Furthermore, the hexagonal boron nitride particles surface-modified with the partially reduced graphene oxide of the present invention can be subjected to an oxidation treatment or reduction treatment to obtain graphene oxide-modified boron nitride particles or reduced graphene oxide-modified boron nitride particles having an adsorption amount that was previously unobtainable.

[0030] By mixing the surface-modified hexagonal boron nitride particles of the present invention with a resin, the thermal properties and mechanical properties of the resin, such as the linear expansion coefficient and thermal conductivity, can be improved. Such physical properties can be improved by mixing the surface-modified hexagonal boron nitride particles with the resin in an amount of 1 to 90% by volume, preferably 10 to 90% by volume, and more preferably 20 to 90% by volume. If the amount is less than 1% by volume, no improvement can be obtained. There is no particular upper limit, but in consideration of the decrease in the mechanical strength of the resin composition, the upper limit is preferably about 90% by volume.

[0031] As a mixing method, when the resin is solid, the resin and the surface-modified hexagonal boron nitride particles are mixed in powder form, and then melt-mixed using a kneader or twin-screw extruder, or the like, or the resin is dissolved in an appropriate solvent and mixed and stirred with the surface-modified hexagonal boron nitride particles, or a dispersion treatment is performed using a homogenizer or bead mill, or a wet process can be performed. These methods can be appropriately selected depending on the properties of the resin used. When the resin is liquid, the resin and the surface-modified hexagonal boron nitride particles can be mixed using a stirrer, three-roll or kneader, or the resin can be diluted with an appropriate solvent or diluent and mixed and stirred with the surface-modified hexagonal boron nitride particles, or a dispersion treatment is performed using a homogenizer or bead mill. These methods can be appropriately selected depending on the properties of the resin used.

[0032] Resins to be mixed with the surface-modified hexagonal boron nitride particles of the present invention include polyolefins, polycycloolefins, polystyrene, ABS, polycarbonates, polyamides, polyimides, polyacrylates, polyethylene terephthalate, polyphenylene sulfide, epoxy resins, urethane resins, silicone resins, phenolic resins, polylactic acid, polyhydroxyalkanoic acid, and the like.

[0033] The resin composition may further contain a curing agent, a crosslinking agent, a polymerization initiator, a polymeric or low molecular compound for adjusting physical properties, and an inorganic filler such as silica or clay, as required. EXAMPLES

[0034] The present invention will be specifically described below with reference to examples, but the present invention is not limited to these examples.

[0035] (Preparation of graphene oxide aqueous dispersion) A 1000ml three-neck flask equipped with a thermometer and a magnetic stirrer was charged with 2.5g of Nippon Graphite UP20, 2.0g of sodium nitrate, and 90ml of concentrated sulfuric acid, and 11.0g of potassium permanganate was slowly added while cooling in an ice bath. After the addition was completed, the mixture was allowed to return to room temperature and stirred for about 96 hours.

[0036] The reaction solution was cooled in an ice bath, 200 ml of 5% aqueous sulfuric acid solution was slowly added, and 50 ml of 30% aqueous hydrogen peroxide solution was added and stirred for 1 hour.Then, the mixture was diluted with 250 ml of a mixture adjusted to a hydrogen peroxide concentration of 0.5% and a sulfuric acid concentration of 3%, and stirred at room temperature for 24 hours. Next, the oxidized graphite was centrifuged. The precipitate was again dispersed in 200 ml of a mixture containing 0.5% hydrogen peroxide and 3% sulfuric acid, and centrifuged again. The centrifuged precipitate was then dispersed in 150 ml of a mixture containing 0.5% hydrogen peroxide and 3% sulfuric acid, and this was placed in a dialysis tube, immersed in ion-exchanged water, and dialyzed for 7 days while exchanging the ion-exchanged water. After dialysis, the dialysate was placed in an ultrasonic cleaner and irradiated with ultrasonic waves for 8 hours, and then centrifuged to remove the supernatant, yielding a graphene oxide aqueous dispersion with a concentration of 0.24 w%. 0.10 g of the dispersion was diluted with 15 ml of distilled water and the UV-visible absorption spectrum was measured, with the maximum absorption peak position at 227 nm. A sample prepared from the dispersion was observed using STEM, and the area of ​​graphene oxide was measured from the STEM image, and the equivalent circle diameter of each graphene oxide was calculated from the area. As a result, the average equivalent circle diameter was 8.13 μm (coefficient of variation 0.77).

[0037] (Preparation of partially reduced graphene oxide aqueous dispersion 1) Next, 0.06 g of ascorbic acid was added to 100 ml of 0.24 w% aqueous graphene oxide dispersion, and reduction treatment was performed at 90° C. for 30 minutes. After cooling the treated solution to room temperature, it was placed in a dialysis tube and immersed in ion-exchanged water, and dialysis was performed for 7 days while exchanging the ion-exchanged water. After dialysis, the dialysate was placed in an ultrasonic cleaner and subjected to ultrasonic irradiation treatment for 30 minutes to obtain aqueous dispersion 1 of partially reduced graphene oxide with a concentration of 0.23 w%. The dispersion was then diluted with distilled water and applied to a silicon plate. Observation with an atomic force microscope (Asylum Research MFP-3D Infinity) revealed that the partially reduced graphene oxide was almost a single layer. The same sample was observed with STEM, and the equivalent area circle diameter was calculated from the obtained microscopic image, giving an average equivalent area circle diameter of 8.22 μm (coefficient of variation 0.82). When 0.16 g of the dispersion was diluted with 15 ml of distilled water and the UV-visible absorption spectrum was measured, an absorption peak was observed at 256 nm.

[0038] (Preparation of partially reduced graphene oxide aqueous dispersion 2) Aqueous dispersion 2 of partially reduced graphene oxide with a concentration of 0.19 w% was obtained in the same manner as in Preparation 1, except that the amount of ascorbic acid was changed to 0.02 g. Observation with an atomic force microscope revealed that the partially reduced graphene oxide was almost a single layer. The average equivalent circle diameter of the partially reduced graphene oxide in the solution was 8.15 μm (coefficient of variation: 0.77), and an absorption peak in the ultraviolet-visible absorption spectrum was observed at 240 nm.

[0039] Example 1 (Preparation of surface-modified flaky hexagonal boron nitride particles 1) In a 50 ml screw-cap bottle, 0.1358 g of the above partially reduced graphene oxide dispersion 1 was diluted with distilled water to 15 ml, and the ultraviolet-visible absorption spectrum was measured. Then, scale-like hexagonal boron nitride particles (Showa Denko SHO-B-N (registered trademark) UHP-2 D) were added to this diluted solution. 500.01 g of 11 μm-average particle size was added, shaken for 1 minute, and allowed to stand. This process was repeated until the amount of the added 0.0511 g was reached, at which point the amount of the supernatant absorbed was 1 / 10 of the original amount, at which point the addition was terminated. The precipitate was then filtered off, washed with 100 ml of distilled water and 100 ml of methanol, and dried at 60°C for 8 hours to obtain a light gray powder (surface-modified UHP-2). If all of the partially reduced graphene oxide used at this point was adsorbed onto UHP-2, the amount of the partially reduced graphene oxide adsorption layer of the surface-modified UHP-2 was calculated to be 0.61 w%.

[0040] (Analysis of surface-modified UHP-2) In order to accurately grasp the amount of the partially reduced graphene oxide adsorption layer for the powder obtained in Example 1, the amount of the partially reduced graphene oxide adsorption layer of the surface-modified UHP-2 was analyzed by quantitative carbon analysis (combustion improver: W and LECOCEL (registered trademark) II, manufactured by LECO) using a carbon / sulfur analyzer (CS844, manufactured by LECO) and found to be 0.63 w% (average value of three measurements). This was the average value of UHP-2 (specific surface area 4 m 2 / g) per unit surface area, 1.58 x 10 -7 g / cm 2 It becomes. Mapping of carbon and boron in a single particle was performed using Auger electron spectroscopy (equipment used: ULVAC PHI700). It was found that where there was a high carbon distribution, there was little boron, and conversely, where there was a high boron distribution, there was little carbon. Carbon was distributed over almost the entire (0001) surface of the particle and over some of the side surfaces. As the carbon originated from partially reduced graphene oxide, it is believed that the partially reduced graphene oxide is adsorbed to a significant portion of the particle. A total of 10 particles were analyzed, and all showed the same trend. Using a Raman microscope, the graphene oxide-derived 1590 cm -1 and the 1360 cm band originating from hexagonal boron nitride particles. -1 The bands of 1590 cm were mapped on most of the observed particle surfaces for 10 particles. -1 A band was detected, which is consistent with the results of Auger electron spectroscopy.

[0041] Comparative Example 1 In a 50 ml screw-cap bottle, 0.1484 g of a 0.24 w% graphene oxide dispersion was diluted to 15 ml with distilled water, and the UV-visible absorption spectrum was measured. Next, 0.01 g of hexagonal hexagonal boron nitride particle powder (UHP-2) was added to this diluted solution, shaken for 1 minute, and allowed to stand. This process was repeated, and when the amount added was 0.1021 g, the absorption of the supernatant became 1 / 10 of the original amount, so the addition was stopped. The precipitate was filtered and washed with 100 ml of distilled water and 100 ml of methanol, and then dried at 60 ° C for 8 hours to obtain a light brown powder. If all the graphene oxide used at this point was adsorbed on UHP-2, the amount was calculated to be 0.35 w% of UHP-2. Next, the amount of graphene oxide adsorbed on UHP-2 was analyzed by quantitative carbon analysis (combustion improver: W and LECOCEL (registered trademark) II) using a carbon / sulfur analyzer (LECO CS844 model). The result was 0.37 w% (average value of three measurements). 2 / g) per unit surface area: 8.72 x 10 -8 g / cm 2 This was 57% of Example 1.

[0042] Example 2 (Preparation of surface-modified plate-shaped hexagonal boron nitride particles 2) In a 50 ml screw-cap bottle, 0.2112 g of the above partially reduced graphene oxide dispersion 2 was diluted with distilled water to 15 ml, and the ultraviolet-visible absorption spectrum was measured. Then, plate-shaped hexagonal boron nitride particles (AR BROWN HSL:D 500.01 g of 100 g of sucrose (average particle size 30 μm) was added, shaken for 1 minute, and allowed to stand. This process was repeated until the addition amount of 0.2011 g was reached, at which point the absorption of the supernatant had become 1 / 10 of the original amount, at which point the addition was terminated. The precipitate was then filtered off, washed with 100 ml of distilled water and 100 ml of methanol, and dried at 60°C for 8 hours to obtain a light grey powder (surface-modified HSL). If it is assumed that all of the partially reduced graphene oxide used at this point has been adsorbed onto the HSL, the amount of the partially reduced graphene oxide adsorption layer of the surface-modified HSL is calculated to be 0.20 w%. This is the same as the amount of HSL (specific surface area 2 m 2 / g) per unit surface area, 1.00 x 10 -7 g / cm 2 It becomes.

[0043] Comparative Example 2 In a 50 ml screw-cap bottle, 0.2421 g of a 0.24 w% graphene oxide dispersion was diluted to 15 ml with distilled water, and the UV-visible absorption spectrum was measured. Next, 0.1 g of hexagonal hexagonal boron nitride particles (HSL) was added to this diluted solution, shaken for 1 minute, and allowed to stand. This process was repeated, and when the amount added reached 2.1133 g, the absorption of the supernatant became 1 / 10 of the original amount, so the addition was stopped. The precipitate was filtered and washed with 100 ml of distilled water and 100 ml of methanol, and then dried at 60 °C for 8 hours to obtain a light brown powder. If all the graphene oxide used at this point was adsorbed by the HSL, the amount was calculated to be 0.022 w% of the HSL. This is the same as the amount of HSL (specific surface area 2 m 2 / g) per unit surface area, 1.37 x 10 -8 g / cm 2 This was 14% of Example 2.

[0044] Example 3 (Preparation of surface-modified granular hexagonal boron nitride particles 3) In a 50 ml screw-cap bottle, 0.2820 g of the above partially reduced graphene oxide dispersion 2 was diluted with distilled water to 15 ml, and the ultraviolet-visible absorption spectrum was measured. Next, granular hexagonal boron nitride particles (Showa Denko SHO-B-N (registered trademark) UHP-G1H:D) were added to this diluted solution. 500.01 g of 100 g of sucrose (average particle size 33 μm) was added, shaken for 1 minute, and allowed to stand. This process was repeated until the addition amount of 0.3203 g was reached, at which point the absorption of the supernatant was 1 / 10 of the original amount, at which point the addition was terminated. The precipitate was then filtered off, washed with 100 ml of distilled water and 100 ml of methanol, and dried at 60°C for 8 hours to obtain a light grey powder (surface-modified G1H). If it is assumed that all of the partially reduced graphene oxide used at this point has been adsorbed onto the HSL, the amount of the partially reduced graphene oxide adsorption layer of the surface-modified G1H is calculated to be 0.27 w%. This is the same as G1H (specific surface area 4 m 2 / g) per unit surface area, 0.67 x 10 -7 g / cm 2 It becomes.

[0045] Comparative Example 3 In a 50 ml screw-cap bottle, 0.2633 g of a 0.24 w% graphene oxide dispersion was diluted to 15 ml with distilled water, and the UV-visible absorption spectrum was measured. Next, 0.1 g of granular hexagonal hexagonal boron nitride particles (UHP-G1H) was added to this diluted solution, shaken for 1 minute, and allowed to stand. This process was repeated, and at the point where 1.085 g was added, the absorption of the supernatant remained at about 90% of the original amount, so it was determined that almost no graphene oxide was adsorbed, and the addition was terminated.

[0046] A comparison between the example in which partially reduced graphene oxide was adsorbed onto boron nitride and the comparative example in which graphene oxide was adsorbed onto boron nitride was as follows. Scaly hexagonal boron nitride particles (Showa Denko Showa B-N (registered trademark) UHP-2 D 50 In Example 1 and Comparative Example 1, in which graphene oxide (average particle diameter 11 μm) was used, the adsorption amount of graphene oxide was 0.37 wt%, while the adsorption amount of partially reduced graphene oxide was 0.63 wt%, which was 1.7 times the adsorption amount. Plate-shaped hexagonal boron nitride particles (AR BROWN HSL:D 50 In Example 2 and Comparative Example 2, in which graphene oxide (average particle diameter 30 μm) was used, the adsorption amount of graphene oxide was 0.022 wt%, while the adsorption amount of partially reduced graphene oxide was 0.2 wt%, which was 9.1 times the adsorption amount. Granular hexagonal boron nitride particles (Showa Denko Showa B-N (registered trademark) UHP-G1H:D 50 In Example 3 and Comparative Example 3, in which boron nitride particles (average particle size: 33 μm) were used, graphene oxide was not adsorbed to the boron nitride particles, but partially reduced graphene oxide was adsorbed in an amount of 0.27 wt %.

[0047] Comparative Example 4 An aqueous dispersion of reduced graphene oxide with a concentration of 0.25 w% was obtained in the same manner as in the aqueous dispersion of partially reduced graphene oxide 1, except that the amount of ascorbic acid was changed to 0.2 g. The reduced graphene oxide in the solution was very prone to aggregation and quickly settled. When the solution was diluted and the UV-visible absorption spectrum of the supernatant was measured, an absorption peak was observed at 270 nm. In a 50 ml screw-cap bottle, 0.1512 g of the above dispersion was diluted to 10 ml with distilled water, to which hexagonal hexagonal boron nitride particle powder (UHP-2) was added and shaken for 1 minute. The reduced graphene oxide aggregated into fine clumps and showed no sign of adsorption to the UHP-2.

[0048] Example 4 (Preparation of resin composition containing surface-modified hexagonal boron nitride particles 1) 1.56 g of solvent-free silicone resin (KNS-320A manufactured by Shin-Etsu Chemical Co., Ltd.) was thoroughly mixed with 2.25 g of the surface-modified UHP-2 prepared in Example 1 and 0.03 g of a curing agent (CAT-PL-50T manufactured by Shin-Etsu Chemical Co., Ltd.) in a mortar. The mixture was placed in a polytetrafluoroethylene square container and vacuum degassed (room temperature for 30 minutes), after which the mixture was covered while being pressed and spread with a polytetrafluoroethylene plate, and the mixture was heated to 80°C for 30 minutes to be cured. The obtained cured product was removed from the mold and cut into a rectangular sample piece measuring 20 mm x 5 mm x 1 mm. Thermomechanical analysis was performed (apparatus used: TA Instruments' DMA Q800) to determine the linear expansion coefficient (room temperature to 100°C), which was 20.8 ppm / K.

[0049] Comparative Example 5 A cured product was prepared in the same manner as in Example 2, except that the surface-modified UHP-2 was replaced with unmodified hexagonal boron nitride particles (Showa Denko's Show-B-N (registered trademark) UHP-2) or hexagonal boron nitride particles with graphene oxide of Comparative Example 1, and the linear expansion coefficient was determined to be 38.0 ppm / K and 26.4 ppm / K, respectively. In addition, the linear expansion coefficient of the solvent-free silicone resin alone cured product was 201 ppm / K. When the results of using unmodified hexagonal boron nitride particles and hexagonal boron nitride particles with graphene oxide of Comparative Example 1 were compared, the latter had a smaller linear expansion coefficient, which is considered to be the result of the improvement in the interfacial adhesion between the hexagonal boron nitride particles and the silicone cured product due to the adsorption of graphene oxide. When these were compared with Example 2, Example 2 had the smallest linear expansion coefficient, suggesting that the interfacial adhesion between the hexagonal boron nitride particles and the silicone cured product was further improved. This is thought to be the result of the partially reduced graphene oxide being well adsorbed, and many parts of the hexagonal boron nitride particles being covered with partially reduced graphene oxide, which has good affinity with the silicone cured product. [Industrial Applicability]

[0050] The surface-modified hexagonal boron nitride particles of the present invention have an improved affinity with resins due to the partially reduced graphene oxide adsorption layer, and can improve the fluidity of the resin composition to which they are mixed and the interfacial adhesion between the hexagonal boron nitride particles and the resin. This makes it possible to provide a resin composition with excellent thermal and mechanical properties, which can be used as a thermal expansion suppressing material and a thermal conductive material for various devices.

Claims

1. Surface-modified hexagonal boron nitride particles, the surface of which is an untreated hexagonal boron nitride particle, having a partially reduced graphene oxide adsorption layer on the surface thereof, the partially reduced graphene oxide adsorption layer exhibiting an absorption peak at wavelengths longer than 230 nm and shorter than 265 nm in an ultraviolet-visible absorption spectrum, and the amount of the partially reduced graphene oxide adsorption layer being 1.5 times or more the amount of the graphene oxide adsorption layer of the surface-modified hexagonal boron nitride particles having the graphene oxide adsorption layer.

2. 2. A method for producing the surface-modified hexagonal boron nitride particles according to claim 1, comprising: adding a reducing agent to the graphene oxide aqueous dispersion to prepare a partially reduced graphene oxide aqueous dispersion; mixing a powder of surface-untreated hexagonal boron nitride particles with the partially reduced graphene oxide aqueous dispersion until the supernatant liquid is no longer colored; recovering the solid from the liquid and drying it; 1. A method for producing surface-modified hexagonal boron nitride particles, comprising:

Citation Information

Patent Citations

  • Carbon-modified boron nitride, production method thereof and high thermal conducting resin composition

    JP2019001701A

  • Method for producing composite

    JP2020180023A